The effects of low-temperature storage on the viability of Lactobacillus casei and the stability of antibacterial activity in green grass jelly synbiotic drinks (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rizal S, Suharyono, Nurainy F, Amela JR. 2020. The effects of low-temperature storage on the viability of Lactobacillus casei and the stability of antibacterial activity in green grass jelly synbiotic drinks. Biodiversitas 21: 3826-3831. Synbiotic drinks from green grass jelly have shown antibacterial activity against pathogenic bacteria. These are usually stored at low temperatures to maintain their characteristics. The aim of this study was to determine the effect of storage at low temperature of 10°C on the viability of lactic acid bacteria (Lactobacillus casei) and the stability of the antibacterial activity in synbiotic drinks made of green grass jelly. Antibacterial activity of green grass jelly synbiotic drink was conducted against pathogenic bacteria (Staphylococcus aureus, Salmonella sp., Bacillus cereus, and Escherichia coli). The products were stored for 28 days at 10°C temperature. Observations on the antibacterial activity, pH value, total acid, and total lactic acid bacteria were carried out every 7 days. Antibacterial activity was evaluated using agar well diffusion method. The results showed that storage at low temperature (10 ± 2°C) for 28 days decreased the antibacterial activity and pH value but sharply increased total lactic acid bacteria (at 0 to 7 days of storage) in green grass jelly synbiotic drinks. Salmonella sp. showed the highest inhibition caused by the antibacterial agents in green grass jelly synbiotic drinks while the lowest inhibition was found on Staphylococcus aureus. During storage at low temperature, green grass jelly synbiotic drinks had a total of lactic acid bacteria that ranged from 9.51 to 10.10 (Log CFU/mL) or equal to 3.24x109-1.26x1010 CFU/mL; a total of lactic acid that ranged from 0.48% to 0.87%; and pH values that ranged from 3.78 to 4.08.
Keywords: Antibacterial activity, green grass jelly, pathogenic bacteria, synbiotic